2020
DOI: 10.1021/acsnano.0c04518
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Activated and Metal–Organic Framework Assisted Self-Assembly of Organic Photosensitizers

Abstract: Tumor accumulation and intratumoral singlet oxygen (1O2) generation efficiency of photosensitizers (PSs) are two essential factors that determine their photodynamic therapy (PDT) efficacies. How to maximize the PS performance at the tumor site is of great research interest. Herein, we report a metal–organic framework (ZIF-8, ZIF = zeolitic imidazolate framework) assisted in vivo self-assembly nanoplatform, ZIF-8-PMMA-S-S-mPEG, as an effective tool for organic PS payloads to achieve efficient PDT. Using an orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…As another kind of typical MOF, a zeolitic imidazolate framework (ZIF-8) was also applied to assist the self-assembly of AIE PSs and improve O 2 transportation, leading to the effective generation of ROS inside tumors for enhanced performance of PDT. 262 Besides TME-activated therapy for cancer, this strategy can also be appropriate for the fabrication of MOF-based nanotheranostics for precise antibacterial therapy and bacterial metabolic labeling, since bacterial infections have seriously threatened human health. Considering the urgent demand for noninvasive theranostic approaches toward bacteria, Kong et al reported MIL-100(Fe)-based nanocarriers for delivery of 3-azido-D-alanine (D-AzAla), which could selectively integrate into the walls of bacteria.…”
Section: Aiegens Hybridizing With Inorganic Nanoparticlesmentioning
confidence: 99%
“…As another kind of typical MOF, a zeolitic imidazolate framework (ZIF-8) was also applied to assist the self-assembly of AIE PSs and improve O 2 transportation, leading to the effective generation of ROS inside tumors for enhanced performance of PDT. 262 Besides TME-activated therapy for cancer, this strategy can also be appropriate for the fabrication of MOF-based nanotheranostics for precise antibacterial therapy and bacterial metabolic labeling, since bacterial infections have seriously threatened human health. Considering the urgent demand for noninvasive theranostic approaches toward bacteria, Kong et al reported MIL-100(Fe)-based nanocarriers for delivery of 3-azido-D-alanine (D-AzAla), which could selectively integrate into the walls of bacteria.…”
Section: Aiegens Hybridizing With Inorganic Nanoparticlesmentioning
confidence: 99%
“…AIE materials provide another ideal choice for bioimaging. Some AIE nanomaterials including supramolecular assemblies, [ 25,26 ] metal–organic frameworks, [ 27 ] silica nanoparticles, [ 28 ] organic nanoparticles, [ 29,30 ] and nanocrystals, [ 31 ] have been developed for cell imaging. TPE based microgels may be another suitable candidates for celling imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the strategies of delicately designed nanoparticles may help to solve these difficulties. A previous study shows that, due to their small size, nanoparticles self-aggregate in a tumor microenvironment with high levels of GSH, thus enhancing tumor retention and accumulation of the nanoparticles [34]. It has also widely been reported that the mechanism by which nanoparticles degrade within the tumor microenvironment accompanies the release of the loaded catalytic enzymes, such as poly(ethylene glycol)-modified glucose oxidase (GOx), to continuously generate •OH and enhance the killing effect of tumor cells [35,36].…”
Section: Discussionmentioning
confidence: 99%